The case study of internationalisation of Polish SME - Borowiak, Lukasz (2011)
This dissertation project analyses the internationalisation processes of Polish medium size enterprise Foliarex. Specifically, the study focuses on two destinations of firm’s foreign activity. The Ukrainian market, where Foliarex established its sales representative and the British market, where the company engaged in indirect exporting. The purpose of this qualitative study is to explain the internationalisation of the company by comparing Foliarex entry strategy into these two markets. The study seeks to analyse the reasons for differences in entry modes employed for these two markets from the perspective of theories and models of internationalisation. The focus of the research will be on the external international environment in which Foliarex operates and firms internal factors – motives and barriers for internationalisation specific for the two markets. The collected empirical data indicates that firm’s decision to internationalise is related to three groups of factors. The first one is the influence of the top manager who plays a considerable role in company’s development. The second set of factors is related to firm’s specific resources which significantly constrain firm’s choices of foreign markets and entry mode selection. Finally, the internationalisation of Foliarex depends on the specific characteristics of a foreign market such as the perspectives for growth and the level of saturation. Overall, various theories and models of internationalisation analysed in this study are only partially able to explain the internationalisation of Foliarex into the UK and Ukrainian markets. The study indicates that only the integration of several theories can explain the internationalisation of the company.